F Studi Deskriptif: "Analisis Efisiensi Instalasi Rawat Inap di Rumah Sakit Islam Surabaya Tahun 2022-2023 dengan Pendekatan Barber Johnson”: Analisis Efisiensi Instalasi Rawat Inap di Rumah Sakit Islam Surabaya Tahun 2022-2023 dengan Pendekatan Barber Johnson - Tamarina, Frea Astrilia; Suswojo, Heru; Absor, Sholihul (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Efficiency is used as an indicator of hospital performance, including the overall performance of hospital health services. The effectiveness of services related to hospital bed management is assessed using the metrics Bed Occupancy Rate (BOR), Average Length of Stay (ALOS), Turnover Interval (TOI), and Bed Turnover (BTO) on the Barachman-Johnson graph. The construction of a new building resulted in an increase in the number of patients and beds from 2022 to 2023, according to medical record data from the Islamic Hospital (RSI) Surabaya inpatient ward. The availability of community services may be affected by changes in bed availability. This study aimed to evaluate the efficiency of inpatient services at RSI Surabaya in 2022–2023 using bed utilization indicators (BOR, ALOS, TOI, and BTO) and the Barber–Johnson graphical approach. This study used an observational analytical design with a quantitative approach. Descriptive and comparative analyses were conducted to evaluate inpatient bed management indicators (BOR, ALOS, TOI, and BTO) at RSI Surabaya in 2022–2023 using the Barber–Johnson method, based on aggregate secondary hospital data.  The RSI Surabaya inpatient ward's Barber Johnson graph for 2022 and 2023 shows that the BOR value has decreased, the ALOS is low, the TOI has reached an optimal value, and the BTO is high. The Barber Johnson efficiency area is not where the four parameter points are located. In conclusion, inpatient bed utilization at RSI Surabaya in 2022 and 2023 did not achieve optimal performance.